Power Series Solution for Korteweg-de Vries Equation - Costa, F. S.; Soares, J. C. A.; Araujo, G. L.; Sousa, M. V. S. (Trends in Computational and Applied Mathematics, 2024)
We apply the similarity method to the Korteweg-de Vries equation, where we obtain a new equation, in terms of similarity variable. We use the power series method, getting the similarity solution, which is exemplified graphically by particular cases.